2012
DOI: 10.5271/sjweh.3328
|View full text |Cite
|
Sign up to set email alerts
|

Relative weight and disability retirement: a prospective cohort study

Abstract: Relative weight and disability retirement: a prospective cohort study by Roos E, Laaksonen M, Rahkonen O, Lahelma E, Lallukka T Severely obese and obese employees have a clearly elevated risk for disability retirement, especially for musculoskeletal causes. The adverse effects of obesity on work ability are partly dependent on co-morbidities and ensuing lowered physical functioning. Promoting the maintenance of normal weight among employees is important as well as the effective treatment of obesity and its co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
4
37
1
Order By: Relevance
“…Parents who reported the above motives as most important had children with higher intake of healthy foods and lower intake of unhealthy foods. In contrast, the food choice motive, convenience, was positively associated with a higher intake of unhealthy foods, suggesting that parents would choose these types of foods because they require little or no preparation [5]. Similarly, another study among 1,095 children ages 12-13 years and their parents showed that sensory appeal was the most important food choice motive, followed by food's health value, convenience in preparation, natural content of foods and foods that helped with weight control.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Parents who reported the above motives as most important had children with higher intake of healthy foods and lower intake of unhealthy foods. In contrast, the food choice motive, convenience, was positively associated with a higher intake of unhealthy foods, suggesting that parents would choose these types of foods because they require little or no preparation [5]. Similarly, another study among 1,095 children ages 12-13 years and their parents showed that sensory appeal was the most important food choice motive, followed by food's health value, convenience in preparation, natural content of foods and foods that helped with weight control.…”
Section: Introductionmentioning
confidence: 90%
“…Nine factors emerged, and were categorized into health, mood, convenience, sensory appeal, natural content, price, weight control, familiarity and ethical concern [9]. Since the original questionnaire by Steptoe, et al was developed to measure the personal motives that underlie food choices of adults, it was modified by Roo, et al to assess motives of foods chosen for the family [5]. The current study used the modified Food Choice Motive questionnaire with seven subscales (food's health value, food's natural content, foods for mood, sensory appeal, price and convenience, foods for weight control, and familiarity of the food).…”
Section: Family Food Choice Motive Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…While not a direct military study, within civilian populations it was shown by Roos et al that overweight males had a musculoskeletal related disability retirement rate 5.6 times more than normal weight males. 55 Females had a rate 11 times higher for musculoskeletal disorders and 2.7 times higher for mental health disorders. 56 All cause disability retirement rates were increased by 1.…”
Section: Military Impacts Of Obesitymentioning
confidence: 99%